1209Physical activity and sitting time across postpartum life stages: A cross-sectional analysis. (2nd September 2021) - Makama, Maureen; Lim, Siew; Skouteris, Helen; Harrison, Cheryce L.; Joham, Anju E.; Mishra, Gita D.; Teede, Helena; Brown, Wendy; Martin, Julie C.; Moran, Lisa J.
Abstract: Background: Physical activity (PA) is beneficial for psychological wellbeing and weight management but is generally low in postpartum women. This study aimed to investigate how PA and sitting time (ST) varied with time since last childbirth. Methods: Data from survey 5 (N = 5219) of the 1973-8 birth cohort (31 – 36 years) of the Australian Longitudinal Study on Women's Health were used to assess association of time since last childbirth (0–6, 7–12 and >12 months) with PA and ST using multiple linear regression. Results: In adjusted model, PA was lower at 0–6 (-238.5METmin/day; 95%CI -319.6, -157.4) and 7–12 (-81.2METmin/day; 95%CI -157.0, -5.5) than >12 months postpartum. ST was longer at 0–6 (0.65hours/day; 95%CI 0.39, 0.91), but not different at 7–12 than at > 12 months postpartum. Overall, higher BMI and being pregnant were inversely associated, while being single, higher stress levels and better self-rated health were positively associated with PA. Conversely, better self-rated health, having more children and breastfeeding were inversely associated, while higher BMI, income and stress levels were positively associated with ST. Conclusion: In the first 6 months, women are less physically active and sit longer than beyond the first postpartum year. This may be due to the high demands of infant feeding/care in early postpartum suggesting a need for additional support to safely resume PA e.g. walking and reduce sitting time. Key message: The first 6 months postpartum is characterized by lower PA and longer ST which may contribute to obesity and chronic diseases.